Multi-language oriented automatic realization method for cryptographic protocols - Xing-hua LI; Shuai-tuan LI; Deng LI; Jian-feng MA (Tongxin xuebao)
A multi-objective-language-oriented automatic code generation scheme for security protocols was put forward.First,based on XML,a description method for security protocols was designed.Second,a graphic user interface(GUI)was developed,through which the XML description documents could be automatically generated by configuring the se-curity protocol.Finally,a security protocol interpreter was designed,through which the corresponding objective code was generated with the XML description document as input.nalysis indicates that compared with the existing schemes the scheme has obvious advantages.